Effect of sorting on shelling efficiency of Bambara nut using shelling machine - Kogh, Donatus Asua; Irtwange, Simon V; Tiough, Daniel Momngu; Anaka, Bill; Gaydaybu , James Flomo (Journal of Postharvest Technology, 2021)
Bambara nut is grown for its edible seeds. Matured seeds are very hard, so have to be soaked in water to soften before shelling and the manual aspect of shelling is time and energy consuming and as such needs the construction of a moderns heller. It is pertinent to mention that this shelling Machine cannot work effectively if the sorting efficiency is not accurate to ensure effective shelling. This study therefore looks at the effect of sorting on shelling efficiency of Bambara nut using Shelling Machine. Within group design was used and the method involved soaking of a bulk quantity of the pods in ordinary water at room temperature for different periods of time thirty minutes for sample I, one hour for sample II and one hour thirty minutes for sample III. The weight of pods that was completely shelled and unbroken (A), completely shelled but broken (B), partially shelled pods (C ) and unshelled pods (D). Result of the finding shows that there was a significant difference in the performance of the machine based on the sorting efficiency. From the result, it was observed that the machine has a very high sorting efficiency and as such, it enhances shelling as it reduces the number of wastages in terms of breakage as well as not shelling. On average, small pods had an average of 3.57 (SD = .220), medium pods had average sorting efficiency of 3.11 (SD = 0.225) while large pods had an average sorting efficiency of 2.57 (SD = .437) thus projecting the machine as having a high level of sorting efficiency. It was recommended that for efficient shelling, Bambara nut should be shelled using the machine that can separate it into various sizes to ensure that the compartments have the right sizes of seeds to ensure effective shelling.